Harnessing the potentials of technology incubation centres (TICs) as tools for fast-tracking entrepreneurship development and actualisation of the Vision 20:2020 in Nigeria. Issue 4 (4th November 2014) - Alam Choudhury, Masudul; A. Akhuemonkhan, Innocent; Raimi, Lukman; M. Patel, Ashok; O. Fadipe, Adeniyi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Entrepreneurship development in Nigeria requires the adoption and assimilation of enterprise development models from nations with replicable success stories. Technology incubation centre (TIC) is one of the potent mechanisms that launched the "BRIC nations" – Brazil, Russia, India and China – to global prominence as the five biggest emerging economies. This paper attempts to unveil the potentials of TICs as novel tools for entrepreneurship development and actualisation of the Vision 20:2020 in Nigeria. Design/methodology/approach – The authors adopt analytical and discursive approaches using qualitative and quantitative data sourced from Industrial policy documents, Goldman Sachs report, online databases of government agencies, Vision 20:2020 policy document and published articles on the subject matter. The generated data were subjected to content and thematic analyses, on the basis of which relevant conclusions were drawn. Findings – The findings from the research indicate that there are 37 TICs in Nigeria with very weak socio-economic impact on job creation, wealth creation and industrial development in Nigeria. However, for the BRIC nations, adopted as comparative models, TICs have impacted positively on job creation, wealth creation and economic development of the five nations. Research limitations/implications – The paper is essentially discursive and subjective. Further research on this subject matter should explore empirical analysis for an objective assessment of the situation. Practical implications – This paper underscores the need for harmonisation of policy objectives with policy implementation. At present, there are gaps between TIC policy objectives and woeful performance of the 37 TICs in Nigeria. Social implications – For Nigeria, to enhance job creation, wealth creation and economic development in the society, there is the need for functional TICs at local, institutional, regional, state and national levels. Originality/value – The paper unveils the gap between economic theory and practical model implementation in developing economy (Nigeria). It is a major contribution to the functionalist and structuralist debates on why policies fail.